Chemistry inquiry conducted by secondary school students into material degradation in the context of sustainability - López-Fernández, María del Mar; Cano-Iglesias, María José; Franco-Mariscal, Antonio Joaquín (Royal Society of Chemistry, 2025)
This study presents an inquiry conducted by ninth-grade secondary school students on material degradation in the context of sustainability. The inquiry is developed as a collaborative project, with students working together throughout most stages, while some tasks such as data collection and analysis were performed individually to encourage autonomy. Furthermore, the inquiry spans a full quarter, enabling students to observe long-term changes, deepen their understanding of the studied processes, and engage more deeply with the environmental issue. Among their key findings, students concluded that a period of 100 days is insufficient for the complete degradation of paper, cardboard, plastic, and metal, with the latter two showing minimal changes despite exposure to environmental conditions that favor photodegradation (solar radiation), thermal degradation (temperature fluctuations between day and night), hydrolytic degradation (humidity variations on rainy days), biodegradation (fungal growth), and chemical degradation or corrosion. Additionally, they developed explanatory models on material degradation, considering environmental factors and their impacts, which allowed them to reflect on sustainability, responsible consumption, and the importance of green chemistry.
Keywords: Educación ambiental; Desarrollo sostenible; Materiales - Deterioro; Estudiantes de enseñanza secundaria; Química; Sostenibilidad; Estudiantes de secundaria